KESALAHAN SISWA DALAM MENYELESAIKAN SOAL STATISTIKA TIPE HIGHER ORDER THINKING SKILLS - Safrida Dwi Damayanti; Agung Hartoyo; Dede Suratman (UNIVERSITAS TANJUNGPURA, 2020)
This study aims to inform student errors in solving statistical problems type HOTS (Higher Order Thinking Skills). There are five varians students ability, that are very high, high, medium, low, and very low. This type of research is a qualitative descriptive study. Subjects in the study involved 36 high school students. The object of this research is the students' errors in solving HOTS type statistical problems. Data collection tecniques used are test tecniques and direct communication teniques (interviews). The results resreach obtained are 3 students with very high ability, 12 students with high ability, 10 students with moderate ability, 6 students with low ability, and 5 students with very low ability to solve statistical problems in the HOTS type. Analytical framework for exposing errors using the Newman method. While the data analysis technique uses qualitative data analysis of Miles and Huberman. Whereas the errors made by students are reading errors (R), comprehension errors (C), transformation errors (T), process skill errors (P), encoding errors (E). The mistakes most students make are process skills errors and encoding errors.Keywords: Error, Higher Order Thinking Skills, Statistika